Reconciling supply-side and secularization: three Scottish Islands - Bruce, Steve (Nordic journal of religion and society (NJRS), 2016)
The sociological secularization thesis and supply-side approach to religious change are associated with competing expectations of the effects of religious diversity; decline in the former and growth in the latter. A systematic comparison of three Scottish islands from 1843 to 2011 shows that the most diverse also saw the greatest decline in religiosity. However, the unusual circumstances of Lewis suggest a partial reconciliation of supply-side and secularization approaches. That the people of Lewis remained religious while those of Orkney and Shetland secularized with the rest of Scotland shows that a de facto religious establishment can benefit from the energy and commitment normally associated with sects competing in a voluntary system.